Case report and literature review: A de novo pathogenic missense variant in ACTN4 gene caused rapid progression to end-stage renal disease - Zhechi He; Ke Wu; Wenqing Xie; Jianghua Chen (Frontiers Media S.A., 2022)
BackgroundFocal segmental glomerulosclerosis (FSGS) is a histopathological diagnosis of the sclerosis of glomeruli and the damage to renal podocytes. FSGS affects the filtration function of the kidneys and results in nephrotic syndrome (NS) in children and adults. FSGS is a clinically and genetically heterogeneous disorder. FSGS-1 [OMIM #603278] is one of the progressive hereditary renal diseases. It is caused by heterozygous variants of the actinin alpha 4 (ACTN4) [OMIM*604638] gene on chromosome 19q13.2 in a dominant inheritance (AD) manner. With the recent development of whole-exome sequencing (WES), 22 (including our case) pathogenic or likely pathogenic variants have been identified in ACTN4 gene.Case presentationWe reported a 17-year-old Chinese girl who was hospitalized with foamy urine, nausea and vomiting. Laboratory tests revealed increased levels of serum creatinine and urea nitrogen. Ultrasonography demonstrated bilaterally reduced size of kidneys. The primary diagnoses were NS and chronic kidney disease stage 5 (CKD5). The hemodialysis was initiated in 48 h after admission. After 4 months of treatment, the patient received an allogeneic kidney transplantation from her father. A novel heterozygous missense variant c.494C > T (p.A165V) in the ACTN4 gene was found by WES in the patient. This variant was confirmed by Sanger sequencing. The computational simulation of the stability of mutant protein (p.A165V) was decreased. Interatomic interactions of the p.A165V site were increased, and it might be associated with the increased ubiquitylation in the vicinity of the mutant site.ConclusionAs per the guidelines of the American College of Medical Genetics and Genomics for interpreting sequence variants, the novel heterozygous missense variant was pathogenic (PS2 + PM1 + PM2 + PP3 + PP4). It should be noted that the early onset of severe proteinuria with a poor prognosis is an important and universal symptom for most genetic FSGS. If necessary, genetic screening is recommended.